The miR-23a/27a/24 − 2 cluster drives immune evasion and resistance to PD-1/PD-L1 blockade in non-small cell lung cancer - Hao Luo; Bin Hu; Xiang-Rong Gu; Jing Chen; Xiao-Qing Fan; Wei Zhang; Ren-Tao Wang; Xian-Dong He; Wei Guo; Nan Dai; Dan Jian; Qing Li; et al. (Molecular Cancer)
Abstract Programmed cell death protein ligand-1 (PD-L1) and major histocompatibility complex I (MHC-I) are key molecules related to tumor immune evasion and resistance to programmed cell death protein 1 (PD-1)/PD-L1 blockade. Here, we demonstrated that the upregulation of all miRNAs in the miR-23a/27a/24 − 2 cluster was correlated with poor survival, immune evasion and PD-1/PD-L1 blockade resistance in patients with non-small cell lung cancer (NSCLC). The overexpression of all miRNAs in the miR-23a/27a/24 − 2 cluster upregulated PD-L1 expression by targeting Cbl proto-oncogene B (CBLB) and downregulated MHC-I expression by increasing the level of eukaryotic initiation factor 3B (eIF3B) via the targeting of microphthalmia-associated transcription factor (MITF). In addition, we demonstrated that the expression of the miR-23a/27a/24 − 2 cluster of miRNAs is maintained in NSCLC through increased Wnt/β-catenin signaling-regulated interaction of transcription factor 4 (TCF4) and the miR-23a/27a/24 − 2 cluster promoter. Notably, pharmacologic targeting of the eIF3B pathway dramatically increased sensitivity to PD-1/PD-L1 blockade in patients with high expression of the miR-23a/27a/24 − 2 cluster in NSCLC. This effect was achieved by increasing MHC-I expression while maintaining high expression of PD-L1 induced by the miR-23a/27a/24 − 2 cluster. In summary, we elucidate the mechanism by which the miR-23a/27a/24 − 2 cluster miRNAs maintain their own expression and the molecular mechanism by which the miR-23a/27a/24 − 2 cluster miRNAs promote tumor immune evasion and PD-1/PD-L1 blockade resistance. In addition, we provide a novel strategy for the treatment of NSCLC expressing high levels of the miR-23a/27a/24 − 2 cluster.